PCR based isolation and cloning of HMW glutenin gene(s) from wheat (T. aestivum var. PBW343) and its fusion with kafirin gene promoter of sorghum - Mishra Avinash (Acta biologica Szegediensis, 2009)
With the aim of grain sorghum improvement to enhance its economic value, HMW glutenin gene subunit(s) were isolated from wheat (T. aestivum var. PBW343) using allele specific primers (AS-PCR) designed on the basis of allelic data available in NCBI Gene Bank. Three glutenin genes viz. Ax1, Dx5 and Dy10 were isolated, cloned, sequenced and analyzed using on line bioinformatics tools. These sequences showed significant homology with the HMW glutenin gene sequences available in the NCBI gene bank. To facilitate transformation of these genes to sorghum, these genes were transferred to a pUC based vector under the regulation of kafirin promoter of sorghum which makes it specific for expression in the endosperm of sorghum. HMW glutenin gene cloned in pGEM vector was excised using restriction enzymes SacI and SacII and directional cloning was performed successfully to clone under the control of kafirin gene promoter of sorghum. Transfer of these gene(s) could be useful for improving the bread making quality of sorghum.